Data hiding mobile application by using encryption and decryption / Nuha Bakizah Mohd Asri - Mohd Asri, Nuha Bakizah (2021)
The phenomenal growth of e-commerce applications in the World Wide Web requires the need to increase the security of data communications over the Internet, especially for highly sensitive document transfer. The main for this techniques which was encryption and decryption were introduced and developed to provide security to these applications. The importance of data security in today’s world cannot be overemphasized. Numerous data security and hiding algorithms have been developed in the last decade. Online attacks have increased to a large extent nowadays and the most common attack among them is data abuse . It is therefore very important that users recognize the fake website and avoid falling prey to it. In this paper, we have proposed a new encryption and decryption system to solve the lack of data hiding problem. Encryption and decryption are used for image-based authentication here. Encode is mainly achieved by changing the message into other code that any third-party will not understand, one with the database of the user and one with the database of the server. And it is only by uploading the image that the original image can be retrieved.